Facility management variables that influence sustainability of building facilities - Ganisen, Shubashini (Penerbit UTM Press, 2015)
Incorporating facility management (FM) knowledge in the building design is essential to increase overall performance of building including quality and cost as; the management and operation process of facilities can have a significant impact on energy, cost, health and safety, and quality. As a result, a more efficient and sustainable facility will be turn over during the post occupancy stage. Thus, this paper explores the consideration of FM during design stage and its influence on achieving sustainability of building facilities in post occupancy phase, and subsequently identifies a set of criteria to evaluate the potential of FM to achieve sustainability of building facilities. A critical review of the literature has been carried out for the purpose of identifying the said variables. Literature review reveals that there is a need to review FM potential of the design during the design phase; mainly due to increased life cycle cost, environmental impact, impact on health and safety and quality of the building facilities during the service life. This paper aims to address the long pending quest of poor awareness of the FM function among the designers and forms the basis for achieving FM sustainability of building facilities